Characterisation of the reaction of 1,4-phenylenebismaleimide with Ca²⁺-ATPase and elucidation of the intramolecular crosslink site - Seekoe, Tshepo W (Division of Chemical Pathology, 2018)
The SR Ca²⁺-ATPase is an ATP driven pump that removes calcium from the sarcoplasm and myofibrils to allow muscle relaxation. The sulfhydryl crosslinker, 1,4- phenylenebismaleimide, reacts with Ca²⁺-ATPase (110 kD) to form a species with an apparent molecular weight of 125 kD, as well as dimers and high order oligomers, on SDS-P AGE. During the course of this study we have optimised and characterised the reaction of 1,4-phenylenebismaleimide with SR Ca²⁺-ATPase to produce the 125 kD species that is reminiscent of an E 125 species formed by intramolecular crosslink with glutaraldehyde. The glutaraldehyde crosslink involves the active site Lys 492 and Arg 678, in a zero distance link that overlaps with the ATP binding pocket, since it can be inhibited by nucleotides. It has been previously shown that the putative intramolecular crosslink with 1,4-phenylenebismaleimide is also sensitive to nucleotide binding. We show that the formation of the putative intramolecular crosslink of SR vesicles ( approximately 20 % of ATPase) with 1,4-phenylenebismaleimide is optimum at alkaline pH with micromolar concentrations of the crosslinker. The formation of ATPase dimers and high order oligomers, which were prominent in the reaction with SR vesicles, were eliminated by solubilising in Triton X-100. Under these conditions and in the presence of calcium, two intramolecular crosslinks are formed as seen in the formation of 125 and 130 kD species. The former seems to be in proximity of the y-phosphate and the latter in the β-phosphate region of the ATP binding site according to nucleotide protection studies. In the presence of detergent (Triton X-100) and absence of calcium, only the 125 kD species is formed and requires stabilisation by thapsigargin, a sesquiterpene lactone that binds the transmembrane α-helices. These conditions yield up to 60 % intramolecularly crosslinked ATPase. Trypsin digestion altered the apparent molecular weight of the 125 kD species to 135 kD, suggesting, in accordance with the results of glutaraldehyde crosslink, that the putative intramolecular crosslink 1s between tryptic fragments A and B. [¹⁴C]1,4-phenylenebismaleimide was synthesised to further characterise the reaction and to elucidate crosslinked amino acid residue following protein digestion, radioactive peptide purification, and sequencing. From filtration studies it was evident that a number of sulfhydryl residues were derivatized in both SR vesicles and solubilised Ca²⁺-ATPase. The results suggests that there is very fast reacting set of sulfhydryl groups, which could comprise of sulthydryls from Ca²⁺-ATPase and/or a minor contaminant protein as previous studies have indicated. Only this fast set was reduced by nucleotide binding. In Triton X-100, the total reactive residues increased two-fold and the biphasic nature of the curve showed that the intramolecular crosslink possibly involves a fast reacting sulfhydryl residue and a slow reacting one. Derivatization with [¹⁴C]1,4-phenylenebismaleimide followed by digestion and HPLC analysis revealed radio labelled peaks. Purification and sequencing of the adducts identified 8 reactive cysteines, namely Cys 12, Cys 344, Cys 364, Cys 471, Cys 498, Cys 636, Cys 670 and Cys 674. The cysteines involved in the putative intramolecular crosslink could not be identified but it is proposed that either Cys 471 or Cys 498 crosslink with Cys 670 or Cys 674.